2020
DOI: 10.1177/0018720819895866
|View full text |Cite
|
Sign up to set email alerts
|

The Ups and Downs of Camera-Monitor Systems: The Effect of Camera Position on Rearward Distance Perception

Abstract: Objective This study investigates the effects of different positions of side-mounted rear-view cameras on distance estimation of drivers. Background Camera-monitor systems bring advantages as compared to conventional rear-view mirrors, such as improved aerodynamics and enlarged field-of-view. Applied research has mainly focused on the comparison between cameras and mirrors or on positioning of in-vehicle monitors. However, the positioning of the exterior camera awaits investigation given that the perspective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 57 publications
2
10
0
Order By: Relevance
“…In sum, the results of the current experiment do not indicate large behavioral changes when slightly displacing the exterior camera in sedans. However, considering the small effects of the low camera position, we stay with the design recommendation formulated earlier (Bernhard & Hecht, 2020): Lower camera positions should be avoided, at least for larger vehicles. Future research should investigate the effects of camera position for larger amounts of vertical displacement as well as the preferences of users in order to identify the most appropriate mounting position of the exterior camera in CMS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In sum, the results of the current experiment do not indicate large behavioral changes when slightly displacing the exterior camera in sedans. However, considering the small effects of the low camera position, we stay with the design recommendation formulated earlier (Bernhard & Hecht, 2020): Lower camera positions should be avoided, at least for larger vehicles. Future research should investigate the effects of camera position for larger amounts of vertical displacement as well as the preferences of users in order to identify the most appropriate mounting position of the exterior camera in CMS.…”
Section: Discussionmentioning
confidence: 99%
“…In other contexts, vertical perspective change has been shown to affect distance and time-to-contact estimation (Daum & Hecht, 2009;Hecht et al, 2015;Leyrer et al, 2015;Ooi et al, 2001;Steward et al, 1993). Effects on distance estimation also generalize to CMS (Bernhard & Hecht, 2020).…”
Section: Introductionmentioning
confidence: 91%
“…As the viewpoint is raised (lowered), stationary observers underestimate (overestimate) their distance to a target. This holds for indoor environments (Corujeira & Oakley, 2013; Gardner & Mon-Williams, 2001; Ooi et al, 2001; Rand et al, 2011; Zhou et al, 2016), virtual environments (Leyrer et al, 2015; Li et al, 2011; Messing & Durgin, 2005), outdoor environments (Daum & Hecht, 2009), restricted viewing conditions (Barfield et al, 1995; Hendrix & Barfield, 1997; Vianin et al, 2004), and CMS (Bernhard & Hecht, 2020). Similar effects might surface in dynamic judgments that precede overtaking maneuvers.…”
Section: Introductionmentioning
confidence: 96%
“…According to the latest numbers, lane change crashes could account for around 4% to 10% of all crashes reported on U.S. roadways (Fitch et al, 2009), and for as much as 17% in Abu Dhabi (Shawky, 2020). Our earlier research indicated that vertical camera displacement affects drivers’ depth perception (Bernhard & Hecht, 2020). The experiment at hand strives to extend these findings with regard to lane change performance and subjective experience in a realistic driving maneuver.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation